2014
DOI: 10.1093/infdis/jiu590
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Parasite DNA as a Measure of Disease Severity in Falciparum Malaria

Abstract: In malaria-endemic areas, Plasmodium falciparum parasitemia is common in apparently healthy children and severe malaria is commonly misdiagnosed in patients with incidental parasitemia. We assessed whether the plasma Plasmodium falciparum DNA concentration is a useful datum for distinguishing uncomplicated from severe malaria in African children and Asian adults. P. falciparum DNA concentrations were measured by real-time polymerase chain reaction (PCR) in 224 African children (111 with uncomplicated malaria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…Similarly to the study by Lamikanra et al, we did find a significant correlation between C T values in the DLM assay for patients with P. falciparum malaria and parasite density determined by microscopy (4). Although the clinical utility of quantitative malaria PCR remains unclear, a recent study by Imwong et al showed that the plasma concentration of P. falciparum DNA correlates with disease severity (18). However, quantitative PCR was performed only on patients who had positive microscopy results in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to the study by Lamikanra et al, we did find a significant correlation between C T values in the DLM assay for patients with P. falciparum malaria and parasite density determined by microscopy (4). Although the clinical utility of quantitative malaria PCR remains unclear, a recent study by Imwong et al showed that the plasma concentration of P. falciparum DNA correlates with disease severity (18). However, quantitative PCR was performed only on patients who had positive microscopy results in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The performance of the RDT at individual sample dilutions to discriminate severe from uncomplicated malaria was then examined in plasma samples from non-pregnant adults ( ≥ 16-year-old) admitted to hospital with slide- or RDT-confirmed falciparum malaria and enrolled in prospective studies at Chittagong Medical College Hospital, Bangladesh (2011); uncomplicated and severe cases were defined using modified World Health Organization criteria [ 17 ]. ELISA methods and results and issues related to ethical permission for testing these samples have been previously described [ 10 , 18 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Our first hypothesis was that S. solidus produces cell-free DNA or cell-bound DNA in the fish abdominal cavity, and that this eDNA could be identified by a PCR approach to correctly detect S. solidus infection in sticklebacks (Bass et al, 2015). eDNA produced by parasites is a common target in epidemiology to detect infection using a PCR approach in organic samples like serum, faeces or plasma (Imwong et al, 2015;Pontes et al, 2002;Xu et al, 2017). eDNA is also used to detect invasive species in aquatic environments (Takahara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%